2015
DOI: 10.4025/actascibiolsci.v37i2.25205
|View full text |Cite
|
Sign up to set email alerts
|

<b>Habitat use by <i>Atherinella brasiliensis</i> (Quoy & Gaimard, 1825) in intertidal zones of a subtropical estuary, Brazil

Abstract: ABSTRACT.Habitat use is different along the ontogenetic development of some species and may be influenced by environmental parameters. This study described the interaction of Atherinella brasiliensis caught in intertidal areas of the Paranaguá Estuarine Complex with environmental parameters. We caught 10024 individuals between August 2010 and July 2011, with total mean length of 44.32 mm (SD ± 25.37 mm), variation range between 12 and 142 mm, and weight between 0.01 and 73 g, averaging 1.35 g (SD ± 2.66 g) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Individual growth rates in fish populations are highly dependent on food availability (Billerbeck et al ., 2001). Several studies have shown that A. brasiliensis changes its prey categories throughout multiple sites in estuaries (Alves et al ., 2016; Carvalho et al ., 2017; Carvalho & Spach, 2015; Contente et al ., 2010b), and this pattern appears to be associated with ecophysiological factors, as described by Cottingham et al . (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual growth rates in fish populations are highly dependent on food availability (Billerbeck et al ., 2001). Several studies have shown that A. brasiliensis changes its prey categories throughout multiple sites in estuaries (Alves et al ., 2016; Carvalho et al ., 2017; Carvalho & Spach, 2015; Contente et al ., 2010b), and this pattern appears to be associated with ecophysiological factors, as described by Cottingham et al . (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ontogenetic development patterns lead to changes in the resources exploited in various generalist fish species (Linke et al ., 2001; Pessanha & Araújo, 2014; Silva et al ., 2016). These niche changes, to capture larger prey due to increased mouth size and individual size, are interpreted as adaptations to the energy demands of fish in different size classes (Carvalho & Spach, 2015; Pessanha & Araújo, 2014; Ross et al ., 2006). This plasticity among different size classes may be a strategy used by fish to avoid intraspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…This species is expected to be abundant in shallow transitional environments, as it is considered an estuarine resident species (Andreata et al, 1990;Araújo et al, 1997). Individuals of all lengths can be caught in these regions throughout the year, as reported by Carvalho and Spach (2015), because this species completes its ontogenetic development in shallow areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite it is not efficiently caught by artisanal fishing, mainly due to the selectivity of the fishing gear used, A. brasiliensis is one of the most abundant species in both coastal and estuarine beach trawls in the south-southeast coast of Brazil (Vilar et al, 2011;Franco et al, 2013). This dominance occurs because the species spends most of its life cycle associated with shallow areas of estuaries, especially in locations with high environmental complexity such as marshes and mangroves (Fávaro et al, 2007;Carvalho and Spach, 2015;Golzio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian Silverside, Atherinella brasiliensis (Quoy & Gaimard, 1854), is a common estuarine resident and generalist species and is abundant in estuaries (Neves et al, 2006;Alves et al, 2016) and others nearshore shallow water ecosystems, as such beaches (Chagas, Junior, 2013;Lacerda et al, 2014;Favero, Dias, 2015), coastal lagoons (Andreata, 2012) and bays (Paiva Filho, Gianinni, 1990;Pessanha, Araújo, 2001;Carvalho, Spach, 2015). Furthermore, A. brasiliensis, show its important in a key structuring role in estuarine food webs (Campos et al, 2015;Figueiredo, Pessanha, 2016), because generalist species are able to feeding and exploit quantitatively on prey from multiple basal nutrient sources (Claudino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%